2016
DOI: 10.1186/s12877-016-0290-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of self-report chronic insomnia disorders with 1–6 month and 6-month durations in home-dwelling urban older adults - the Shih-Pai Sleep Study in Taiwan: a cross-sectional community study

Abstract: BackgroundTo examine the correlates of insomnia disorder with different durations in home-dwelling older adults.MethodsA cross-sectional survey in the Shih-Pai area of Taipei City, Taiwan (The Shih-Pai Sleep Study). A total 4047 subjects over the age of 65 years completed the study (2259 men and 1788 women). The Pittsburgh Sleep Quality Index and the duration of insomnia symptoms were used to identify DSM-IV 1–6 month and 6-month insomnia disorders.ResultsThe prevalence of DSM-IV defined insomnia disorder was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…The results of gender differences in the prevalence studies of insomnia have been mixed. Some studies found that women suffered from insomnia more frequently than men (8,18,19), while opposite findings were found in other studies (28). A previous meta-analysis of cross-sectional studies (29) found that women had a higher risk of insomnia [risk ratio (RR) = 1.41].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of gender differences in the prevalence studies of insomnia have been mixed. Some studies found that women suffered from insomnia more frequently than men (8,18,19), while opposite findings were found in other studies (28). A previous meta-analysis of cross-sectional studies (29) found that women had a higher risk of insomnia [risk ratio (RR) = 1.41].…”
Section: Introductionmentioning
confidence: 98%
“…In order to reduce its adverse outcomes and allocate appropriate health resources, health professionals and policymakers need to understand the patterns and clinical features of insomnia. Prevalence of insomnia in the general population varies greatly across studies, ranging from 5.8 to 32.8% (18)(19)(20)(21), and is associated with certain demographic factors, such as age, gender, marital status, income, and education level (22).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that insomnia is often found in women [36] and the sleep quality is worse than in men [37]. However, this study did not clearly show the relationship between gender and the sleep quality, although it is reported that there is a relationship between insomnia and bodily pain [35] [36], it was not clarified in this study.…”
Section: Discussionmentioning
confidence: 59%
“…← Click for updates doi: 10.7243/2056-9157- Other previous studies have shown that the aging process is often accompanied by diminished sleep quality and irregular sleep patterns [3][4][5], and that as age increases, physical HRQOL declines [6][7][8]. Furthermore, sleep problems were significantly correlated with chronic diseases, such as depression [5,9], heart diseases [5,9,10], arthritis [5,9,10], and lung diseases [9,10]. It was also reported that the presence of chronic or serious diseases significantly lower HRQOL [11][12][13].…”
Section: Crossmarkmentioning
confidence: 99%